Protocol for genetic analysis of population-scale ultra-low-depth sequencing data - Jingyu Zeng; Linxuan Li; Ying Lin; Xianmei Lan; Xinyi Zhang; Yingying Wang; Mingzhi Liao; Xin Jin; Huanhuan Zhu (STAR Protocols)
Summary: Non-invasive prenatal testing (NIPT) not only enables the detection of chromosomal anomalies in fetuses but also generates vast amounts of ultra-low-depth sequencing data, which can be leveraged for population genomic studies. Here, we present a protocol designed for massive ultra-low-depth sequencing datasets. We detail the steps for data processing, quality control, and genotype imputation, followed by genome-wide association study (GWAS) and post-GWAS analyses. This protocol applies to a wide range of ultra-low-depth sequencing studies, extending beyond data from NIPT.For complete details on the use and execution of this profile, please refer to Xiao et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.